Visual and olfactory preferences of Frankliniella occidentalis (Thysanoptera: Thripidae) for color and volatiles of different Rosa chinensis (Rosales: Rosaceae) cultivars. (3rd July 2022) - Zhang, Changrong; Wang, Chun; Maggi, Filippo; Li, Shuai; Meng, Yonglu; Luo, Shuangli; Yang, Siyu; Cao, Yu
ABSTRACT: The free choice of Frankliniella occidentalis to the paper color simulative to Rosa chinensis cultivars (Ruby, Love, Parade, Mohana, Pink Peace, and Spectra) was tested in Petri dishes, and their behavioral responses to the volatiles of different these R. chinensis cultivars was tested in a Y-tube olfactometer. The results showed that F. occidentalis exhibited color preference for yellow (Mohana ≈ Spectra) > red (Ruby ≈ Love) > pink (Parade ≈ Pink Peace), whereas the preference for plant flower volatiles was Ruby > Love > Parade > Mohana > Pink Peace > Spectra. Gas chromatography mass spectrometry analysis showed that benzeneethanol was the single most abundant component in the volatile profiles of Ruby, Love, and Mohana, with contents of 37.03, 25.25, and 33.13%, respectively. (Z)-3-Hexenyl acetate was the most abundant component in the volatile profiles of Parade and Spectra, with contents of 39.87 and 22.62%, respectively. Geraniol (16.07%) was the most abundant component of the Pink Peace volatiles. Therefore, future mitigation approaches, e.g., color sticky traps or/and attractants, could be still used for the key monitoring and control of F. occidentalis on a particular cultivar when different varieties of certain crops were grown together on a large scale.